Portability of Pension Rights in the EurAsEC Countries and the European Union - Anna Almakaeva; Veronika Kostenko (Journal of Economic Sociology, 2014)
National pension systems in EurAsEC countries differ significantly in their structure, pension age and social taxes. At the same time, dramatically increasing migration flows raise the issue of proper coordination of various schemes and portability of pension rights. The current study gives an overview of the existing law regulations and identifies two major schemes of portability — geographical and proportional. Geographical portability established in 1992 calculates the pension provision according to the laws of the country of residence. It prevails in EurAsEC and regulates the relations between Russia, Kazakhstan, Kyrgyzstan and Tajikistan. It does rather poor taking into account unequal migration flows, multi-pillar and heterogeneous pension systems. Proportional portability established in 2007 regulates the relation between Russia and Belorussia and calculates pension provision according to the laws of the country where a pensioner worked. It has been used in the European Union for decades and ensures effectively from labor mobility loses. The study puts a strong argument in favor of proportional system and emphasizes the need of expanding its regulatory power for all EurAsEC countries.